2020
DOI: 10.1002/jmri.27266
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approach for Anterior Cruciate Ligament Lesion Detection: Evaluation of Diagnostic Performance Using Arthroscopy as the Reference Standard

Abstract: Background: MRI is the most commonly used imaging method for diagnosing anterior cruciate ligament (ACL) injuries. However, the interpretation of knee MRI is time-intensive and depends on the clinical experience of the reader. An automated detection system based on a deep-learning algorithm may improve interpretation time and reliability. Purpose: To determine the feasibility of using a deep learning approach to detect ACL injuries within the knee joint on MRI. Study Type: Retrospective. Population: In all, 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 34 publications
(63 reference statements)
0
28
0
Order By: Relevance
“…Not only in the field of OA, 3D CNN has also been applied in detecting anterior cruciate ligament (ACL) injuries from MR images [ 72 ]. Moreover, ACL damage has been known to be a high-risk factor of knee OA.…”
Section: Application Of 3d Deep Learning In Knee Osteoarthritis Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only in the field of OA, 3D CNN has also been applied in detecting anterior cruciate ligament (ACL) injuries from MR images [ 72 ]. Moreover, ACL damage has been known to be a high-risk factor of knee OA.…”
Section: Application Of 3d Deep Learning In Knee Osteoarthritis Assessmentmentioning
confidence: 99%
“…Moreover, ACL damage has been known to be a high-risk factor of knee OA. Zhang et al [ 72 ] have demonstrated that 3D DenseNet outperformed VGG16 and ResNet due to its low complexity and excellent anti-overfitting performance.…”
Section: Application Of 3d Deep Learning In Knee Osteoarthritis Assessmentmentioning
confidence: 99%
“…Knee injuries account for the largest percentage of sport-related, severe injuries (i.e., injuries that cause more than 21 days of missed sport participation) [ 1 , 2 , 3 , 4 ]. Anterior cruciate ligament (ACL) ruptures represent more than 50% of the cases, affecting 200,000 individuals in the United States each year [ 1 , 5 , 6 , 7 ]. Knee cartilage lesions affect around 900,000 individuals in the United States every year, resulting in over 200,000 surgical procedures [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, a study described a customized CNN for diagnosing ACL tears using sagittal fat-suppressed proton densityweighted 1.5-T and 3-T MR images [13]. The CNN achieved a sensitivity of 98%, specificity of 94%, and accuracy of 96%.…”
Section: Introductionmentioning
confidence: 99%